RhoGAP domain-containing fusions and PPAPDC1A fusions are recurrent and prognostic in diffuse gastric cancer. Issue 1 (December 2018) - Yang, Hanna; Hong, Dongwan; Cho, Soo; Park, Young; Ko, Woo; Kim, Ju; Hur, Hoon; Lee, Jongkeun; Kim, Su-Jin; Kwon, Sun; Lee, Jae-Hyuk; Park, Do; et al.
Abstract We conducted an RNA sequencing study to identify novel gene fusions in 80 discovery dataset tumors collected from young patients with diffuse gastric cancer (DGC). Twenty-five in-frame fusions are associated with DGC, three of which (CLDN18-ARHGAP26, CTNND1-ARHGAP26, andANXA2-MYO9A ) are recurrent in 384 DGCs based on RT-PCR. All three fusions contain a RhoGAP domain in their 3' partner genes. Patients with one of these three fusions have a significantly worse prognosis than those without. Ectopic expression ofCLDN18-ARHGAP26 promotes the migration and invasion capacities of DGC cells. Parallel targeted RNA sequencing analysis additionally identifiesTACC2-PPAPDC1A as a recurrent and poor prognostic in-frame fusion. Overall, PPAPDC1A fusions and in-frame fusions containing a RhoGAP domain clearly define the aggressive subset (7.5%) of DGCs, and their prognostic impact is greater than, and independent of, chromosomal instability andCDH1 mutations. Our study may provide novel genomic insights guiding future strategies for managing DGCs. Diffuse Gastric Cancer (DGC) is increasingly being considered separate to intestinal type gastric cancer; several fusions events have been reported as drivers of the disease but few of those have been subsequently validated. Here the authors perform RNA-seq on early-onset DGC patients who had not been treated with chemotherapy or radiation and identify a previously unknown fusion.